2011
DOI: 10.1021/es201269j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Concentration of CO2 and SO2 on the Absorption of CO2 by a Lithium Orthosilicate-Based Absorbent

Abstract: A novel, high temperature solid absorbent based on lithium orthosilicate (Li(4)SiO(4)) has shown promise for postcombustion CO(2) capture. Previous studies utilizing a clean, synthetic flue gas have shown that the absorbent has a high CO(2) capacity, >25 wt %, along with high absorption rates, lower heat of absorption and lower regeneration temperature than other solids such as calcium oxide. The current effort was aimed at evaluating the Li(4)SiO(4) based absorbent in the presence of contaminants found in typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…However, SO 2 may inhibit the adsorption of CO 2 , which was validated by Pacciani et al . , concluding that exposed Li 4 SiO 4 sorbents in a low‐concentration SO 2 flow exhibited an irreversible reaction, with a decrease in CO 2 capacity. Moreover, SO 2 may be oxidized to SO 3 , which may adsorb in the form of a stable sulfate.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, SO 2 may inhibit the adsorption of CO 2 , which was validated by Pacciani et al . , concluding that exposed Li 4 SiO 4 sorbents in a low‐concentration SO 2 flow exhibited an irreversible reaction, with a decrease in CO 2 capacity. Moreover, SO 2 may be oxidized to SO 3 , which may adsorb in the form of a stable sulfate.…”
Section: Resultsmentioning
confidence: 91%
“…Alternatively, doping Li 4 SiO 4 with different heteroatoms (Al or Fe ) produced interstitial Li + sites, or anionic vacancies, resulting in improved diffusion kinetics. Furthermore, it was observed that different water vapor concentrations and temperatures led to different reaction kinetics for Li 4 SiO 4 , and the presence of SO 2 generated an irreversible reaction with Li 4 SiO 4 , forming Li 2 SO 4 , which inhibited the CO 2 adsorption process . Observably, the kinetics of CO 2 adsorption on Li 4 SiO 4 can be examined in a suitable experimental design; however, obtaining experimental data on the intermediate structures and detailed adsorption process is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons may be that SO 2 absorption process was controlled by the gas film, high concentrations of CO 2 in the mixture involved in chemical equilibrium process, thereby increasing SO 2 gas phase mass transfer resistance and impact absorption rate of SO 2 . [18][19][20] Oxygen in the air increased the oxidation to SO 2 and removal efficiency was enhanced, dilution of sulfur dioxide with air instead of nitrogen also reduced the energy consumption, therefore the removal efficiency from the mixture of SO 2 + air topped out. Initial SO 2 concentration.-Gas pollutant concentrations often change in dynamic range, so two different sulfur dioxide concentrations were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al (2012) found that the addition of 12e18% steam into feed gas at 575 C enhanced the CO 2 chemisorption capacity of Li 4 SiO 4 by 60% in 30 min, compared with absorption without steam. However, Pacciani et al (2011) noticed that the effect of increasing [H 2 O] from 10 to 40 vol% on both CO 2 absorption capacity and absorption rate of Li 4 SiO 4 was relatively minor. The presence of water vapor reduces the absorption temperature window of aLi 5 AlO 4 .…”
Section: Effect Of Steammentioning
confidence: 99%